The Structure of Simple General Equilibrium Models with Frictional Unemployment - Davidson, Carl; Martin, Lawrence; Matusz, Steven (Journal of Political Economy, 1988)
We develop a two-sector general equilibrium model in which equilibrium unemployment arises endogenously because of trading frictions in the labor market of one sector. Externalities inherent in the search process lead to inefficient equilibria, and this has important implication for the basic structure of the economy. In particular, the relationship between factor rewards and commodity prices is fundamentally different from the analogous relationship in a frictionless economy. One implication is that the economy's relative supply curve may be downward sloping, especially when the search sector is small. We also present several applications of the analysis.